PHYTOREMEDIATION STUDIES OF SELECTED PLANT SPECIES ON BIOAVAILABILITY AND HYPER ACCUMULATION OF CADMIUM FROM CONTAMINATED SOIL - MUHAMMAD, K.S.; M. GARBA; M. A. USMAN; A. MUSA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
Soil and water contaminated with toxic heavy metals posed significant environmental and human health hazards that are still in need of an effective and affordable biotechnological solution. Phytoremedial analysis of soil sample contaminated with cadmium has been carried out using different species of plants with the aim of finding a solution towards a method that could effectively mitigate the degree of soil contamination due to toxic heavy metals. This process was achieved through a controlled experiment carried out in a green house. The soil sample used was treated accordingly and spiked with 1% of cadmium inform of cadmium nitrate to achieve a significant level of contamination. Ten different plant species were planted separately in a plastic vase containing the contaminated soil and allowed to grow along side with control for the period of eight weeks. After harvesting, the plants were sorted into root, stem and leaves. The cadmium content of each part was analysed using Atomic Absorption Spectrophotometric (AAS) method of analysis. The result indicated that the shoot of Ricinus communis accumulated the highest concentration of cadmium (686.463  0.0028mg/kg), followed by that of Azadirachta indica (678.888  0.0031mg/kg) and Senna occidentalis demonstrated the lowest level of cadmium accumulation (11.6500.0005mg/kg). But with respect to the accumulation in the root and stem, Azadirachta indica has shown the highest cadmium levels of 533.577  0.0035mg/kg and 582.013  0.0018mg/kg respectively, while the lowest level in the root was recorded in Amaranthus spinosa.(30.922 0.0003mg/kg) and the stem of Jatropha curcas accumulated the least mean level of 23.634 0.0007mg/kg. The results obtained indicated that the concentrations of cadmium in the parts of the plants grown in the contaminated soil were greater than those grown in the unspiked soil as control. It is therefore suggested that the analysed plant species could be potentially useful in the immobilisation, phytoextraction and subsequent removal of cadmium from the contaminated soil.